Hubungan Kompetensi Pedagogik dan Kemampuan Mengelola Pembelajaran pada Guru SD se-Kecamatan Pacitan - Nanda Eka Saputri; Kartika Chrysti Suryandari; Ratna Hidayah (Universitas Sebelas Maret, 2021)
AbstractThe study aimed to prove positive correlation between pedagogical competence and classroom management skill to public elementary school teachers in Pacitan Sub-district and to measure the contribution of pedagogical competence and classroom management skill to elementary school teachers in Pacitan Sub-district. It was correlational quantitative method. The population were 222 elementary school teachers of first to sixth grade and the samples were 144 teachers. Data collection techniques used questionnaire. The prerequisite test used linearity and normality tests. Data analysis used a simple correlation test and adjusted R square. The results showed that there was positive correlation between pedagogical competence and classroom management skill. The correlation value was 0,335 and it indicated as moderate correlation. Pedagogical competence contributed 11.2% on classroom management skill. High pedagogical competence was closely related to how teachers: understanding student characteristics, understanding theories and learning principles, developing curriculum, presenting enlightened learning, developing student potency, having good communication to students, and conducting evaluations and assessments measuring the success of learning process. Therefore, if teacher’s pedagogical competence was good, the classroom management would be maximized.